A numerical study of film condensation on a metallic foam-sintered plate with considering convection and super-cooling effects. (December 2016) - Qu, Z.G.; Li, A.; Tao, W.Q.
Abstract: A numerical solution was presented for film condensation on a vertical plate sintered with metallic foam. In the metallic foam region, the Brinkman-Darcy model was employed to establish the fluid flow equation, and the thermal equilibrium model was used to describe local heat transfer. Through introduction of dimensionless distance, namely, the ratio of the coordinate normal to the plate and the local film thickness, the computational domain was regularized in a rectangular zone. The effects of convection and explicit heat of super-cooled liquid on the condensation film were considered. The temperature and velocity profile, film thickness, and the local and average Nu number were obtained. The effects of Ja and Da number on the velocity profile and heat transfer performance were investigated. The numerical model was verified through comparison of the predicted results with those in the literature, which neglected convection and explicit heat of super-cooling effects. Convection and explicit heat of super-cooling can play a positive role in reducing the velocity level in the film. The two effects played a positive role in heat transfer improvement when the dimensionless location along the gravity direction (X) was > 0.15, which was associated with reduced film thickness. The two effects also had a mild influence on the linear distribution of dimensionless temperature. The heat transfer performance deteriorated with an increase in Ja number or Da number.